Practicality of modular construction: experience of the past and prospects - Novik, Hanna; Gnatiuk, Liliia; Vizir, Anhelina (Theory and practice of design, 2022)
The purpose of this article: to determine the practical value of modular construction on the basis of examples of erected modular buildings. To find out the expediency of using modular technology in our time, paying special attention to current events in Ukraine. Analyze the prospects for the development of modular construction. Methodology. General scientific methods are used, such as analysis, systematization, generalization, comparison. The empirical basis for scientific work was remote analysis of objects: scientific publications and articles. Results. The article examines the features of the technological process of construction of buildings on modular technology. The differences between the main characteristics of traditional and modular construction are outlined. A number of Ukrainian and foreign sources dealing with this problem have been studied. To create an idea of the practical significance of the erected modular buildings, the history of the development of the modular method of construction was studied, and well-known examples of architectural solutions were analyzed. In particular, the hospital designed by Isambard Kings Brunel during the Crimean War, George Nelson’s Experimental House, Habitat 67, Leishenshan Hospital in Wuhan and modular homes for internally displaced Ukrainians. It was found that modular technology reduces the im-pact of construction on the environment, accelerates the pace of construction, saves time and materials. It was found that modular construction was most often used in response to significant social and natural challenges. Some key recommendations for the design of modular temporary housing for internally displaced persons in Ukraine are highlighted